2009
DOI: 10.1007/s10165-009-0164-2
|View full text |Cite
|
Sign up to set email alerts
|

Leukocytapheresis (LCAP) decreases the level of platelet-derived microparticles (MPs) and increases the level of granulocytes-derived MPs: a possible connection with the effect of LCAP on rheumatoid arthritis

Abstract: Microparticles (MPs) are believed to play an important role in inflammatory diseases such as rheumatoid arthritis (RA). Leukocytapheresis (LCAP) is one of the options available for the treatment of RA. We analyzed the levels of MPs in RA, by flow cytometry, especially in relation to the effect of LCAP. Twenty female patients with RA were recruited into this study. Six of the 20 patients with RA further received LCAP. Plasma levels of platelet-derived MPs were high in patients with RA and are correlated with di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
12
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 34 publications
2
12
0
Order By: Relevance
“…Recent report showed PE combined with LCAP is effective to induce remission for the patient with steroid, CsA, and PE refractory sJIA . The mechanism of the efficacy of LCAP remains obscure, but removal of activated inflammatory cells, reduction of plasma microparticles are suspected to be effective for MAS . In our patient, PE + LCAP reduced the number of peripheral WBC and serum levels of inflammatory cytokines, as well as previous reports.…”
Section: Discussionsupporting
confidence: 85%
“…Recent report showed PE combined with LCAP is effective to induce remission for the patient with steroid, CsA, and PE refractory sJIA . The mechanism of the efficacy of LCAP remains obscure, but removal of activated inflammatory cells, reduction of plasma microparticles are suspected to be effective for MAS . In our patient, PE + LCAP reduced the number of peripheral WBC and serum levels of inflammatory cytokines, as well as previous reports.…”
Section: Discussionsupporting
confidence: 85%
“…In this study, we identified for the first time PD-1 expression by EVs and owing to the suggested role of this protein and EVs in RA pathogenesis (3235), we further characterized the PD-1 expression in EVs in RA patients. Exhausted T cells are associated with chronic inflammatory diseases, including RA (36).…”
Section: Discussionmentioning
confidence: 99%
“…Platelets and platelet-derived microparticles have been associated with inflammatory processes of autoimmune disorders including rheumatoid arthritis, systemic lupus erythematosus and sjögren syndrome [14], [22][27]. The study of the pathogenesis of these platelet-derived microparticles has increased over the last decade, and multiple mechanisms have been proposed [14], [23], [24], [27].…”
Section: Discussionmentioning
confidence: 99%
“…The study of the pathogenesis of these platelet-derived microparticles has increased over the last decade, and multiple mechanisms have been proposed [14], [23], [24], [27]. Platelet-derived microparticles have been directly involved with leukocyte activation, monocytes in particular, during inflammation [28].…”
Section: Discussionmentioning
confidence: 99%